2017
DOI: 10.2147/copd.s148422
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of long-term noninvasive positive pressure ventilation in stable hypercapnic COPD patients with respiratory failure: a meta-analysis of randomized controlled trials

Abstract: IntroductionThe efficacy of long-term noninvasive positive pressure ventilation (NPPV) in stable hypercapnic COPD patients with respiratory failure remains unclear. The aim of this meta-analysis was to critically assess the efficacy of long-term NPPV on mortality, acute exacerbation, exercise capacity, symptoms and significant physiological parameters (lung function, respiratory muscle function and gas exchange).Patients and methodsWe performed an electronic literature search using the PubMed, Cochrane Library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Finally, while the first studies of long-term non-invasive ventilation in COPD patients were disappointing, two more recent trials found a survival benefit in markedly hypercapnic patients who had been admitted for respiratory failure. What these studies had in common was the relatively high-pressure settings and ambitious targets in terms of partial pressure carbon dioxide (PaCO 2 ) reduction 69 .…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…Finally, while the first studies of long-term non-invasive ventilation in COPD patients were disappointing, two more recent trials found a survival benefit in markedly hypercapnic patients who had been admitted for respiratory failure. What these studies had in common was the relatively high-pressure settings and ambitious targets in terms of partial pressure carbon dioxide (PaCO 2 ) reduction 69 .…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…In patients with obesity hypoventilation syndrome, recent data suggest that NIV and CPAP results in a similar improvement in arterial blood gas measurement and health-related quality of life 62. A meta-analysis assessing the efficacy of long-term NIV in patients with COPD has shown that the arterial PaO 2 of carbon dioxide (PaCO 2 ) can be decreased with NIV with mortality improved with a significant reduction in PaCO 2 by NIV 63. This is supported by recent studies that have demonstrated that effective NIV, with the aim of significantly reducing elevated PaCO 2 , is well tolerated and associated with improvements in quality of life64 and long-term survival 65.…”
Section: Home Management Of Chronic Respiratory Failurementioning
confidence: 99%
“…Although all-cause mortality alone was not reduced in this study (adjHR 0.67 95%CI 0.34; 1.30; P=0.23), home-based NIPPV significantly prolonged time to readmission or death from 1.4 months to 4.3 months (table 1). A more recent meta-analysis of NIPPV and bilevel PAP therapy in stable patients with COPD in 2017 by Liao and colleagues reported no significant difference in mortality [33]. However, in a subgroup analysis involving studies that demonstrated a significant reduction in hypercapnia, there was a reduction in mortality [33].…”
Section: Scientific Literature In Support Of Home-based Ventilatory Smentioning
confidence: 99%
“…A more recent meta-analysis of NIPPV and bilevel PAP therapy in stable patients with COPD in 2017 by Liao and colleagues reported no significant difference in mortality [33]. However, in a subgroup analysis involving studies that demonstrated a significant reduction in hypercapnia, there was a reduction in mortality [33]. Moreover, studies with higher levels of pressure assist were more likely to yield favorable effects and these were more likely to be studies performed in Europe (table 1).…”
Section: Scientific Literature In Support Of Home-based Ventilatory Smentioning
confidence: 99%
See 1 more Smart Citation